Respostas neuroendócrinas de um modelo experimental de ataque de pânico - Armini, Rubia de Souza (2012)
In humans, spontaneous and lactate-induced panic attacks (PA) are not accompanied by the increase in the ‘stress hormones’ corticotropin (ACTH), corticosterone (CORT) and prolactin (PRL). Previous studies showed in turn that the 'stress hormones' remain unchanged changed following the defensive behaviors induced by electrical stimulation of the dorsal periaqueductal gray matter (DPAG) of rats. However, the CORT morning basal levels of these rats were about 300 ng/ml, which are much higher than the expected 60-100 ng/ml. Although the CORT baseline level bears no relationship with PRL responses, they could explain the lack of ACTH responses. Indeed, other researchers reported significant increases in CORT plasma levels 30 min after DPAGevoked escape responses. Yet, it remains unclear whether the latter results were due to the muscle exertion or emotional response. Therefore, the present study both examined the laboratory routines influencing the basal secretion of stress hormones (Study I) and reexamined the stress hormone responses to DPAG stimulations of same intensities in arenas with diameters either large (60 cm) or small (20 cm), in which trotting and galloping are supressed. Result of Study I showed that daily handling and repeated exposures to the arena sensitize the neuroendocrine responses. In turn, the Study II corroborated the previous studies with stimulation in the large arena and showed that rats with reduced CORT baseline levels failed in presenting any neuroendocrine responses following the DPAG stimulation in the small arena with the flight 6 threshold intensity recorded in the large arena. These results support the DPAG-evoked responses as a model of PA.